2012
DOI: 10.1002/hbm.22064
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced resting-state oscillations in schizophrenia are associated with decreased synchronization during inattentional blindness

Abstract: Patients suffering from schizophrenia have been characterized by an apparent lack of theta (around 6 Hz) and gamma (>40 Hz) brain oscillatory activity during task execution. The neurocognitive reasons for these abnormal synchronization patterns, however, remain elusive. Recording the electroencephalogramm (EEG) during a selective visual attention task, the current study investigates whether abnormal brain oscillatory resting-state activity in the theta band might account for a lack of task-related brain oscill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 40 publications
3
28
0
Order By: Relevance
“…2C). The mainly theta frequency (ϳ7 Hz) ongoing activity observable in the passive condition was significantly larger in patients (see also Hanslmayr et al, 2012) and showed a frontocentral maximum in topographic maps consistent with at least partly auditory generators (Fig. 5A-C).…”
Section: Task-related Modulation Of Theta/alpha Activitymentioning
confidence: 78%
See 2 more Smart Citations
“…2C). The mainly theta frequency (ϳ7 Hz) ongoing activity observable in the passive condition was significantly larger in patients (see also Hanslmayr et al, 2012) and showed a frontocentral maximum in topographic maps consistent with at least partly auditory generators (Fig. 5A-C).…”
Section: Task-related Modulation Of Theta/alpha Activitymentioning
confidence: 78%
“…Even though, as our results suggest, the suppression of neuronal excitability predominates in auditory cortical regions at critical time points, this only serves to attenuate ignored frequency content and enhance the sensory representation of attended stimuli. As opposed to this, the goal of automatic or passive predictive processes is to suppress selfgenerated or frequently occurring nonrelevant items, and only signal whether a change is detected (Houde et al, 2002;Friston, 2005;Baldeweg, 2006;Bäss et al, 2008;Winkler et al, 2009;Chen et al, 2011;Costa-Faidella et al, 2011;Knolle et al, 2013). In these cases, an inverse pattern would be ideally suited as the mechanism: oscillations entrained with their suppressive phases could be centered on the spectrotemporal properties of selfgenerated or frequently occurring nonrelevant sounds, while the rest of auditory cortex could be entrained with their opposing, high-excitability phases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This synchronization is observed in oscillatory activity recorded by EEG and MEG and refers to a consistent relation between the phases of the oscillatory activity of two brain regions that can be assessed from the measured time series . Recent studies on a host of neurological disorders including Alzheimer's disease (de Haan et al, 2012;Tahaei et al, 2012), Parkinson disease (Babiloni et al, 2011;Bosboom et al, 2009;Stoffers et al, 2008), schizophrenia (Hanslmayr et al, 2012;Hinkley et al, 2011;Jalili et al, 2007) and epileptic seizures (Mormann et al, 2003;Stam et al, 2007a) have demonstrated a disruption in this synchronization in various frequency bands. In MDD, impairments in synchronization in both y and a bands have been reported (Fingelkurts et al, 2007;LinkenkaerHansen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Recent resting state electroencephalogram (EEG) showed increased coherence in basically all low-and high-frequency bands including delta, theta, alpha, and gamma bands within and between hemispheres in schizophrenia. [29][30][31][32][33] Most interestingly, the study by Spencer 33 could relate the increased gamma power in auditory cortex to reduced stimulusevoked activity in response to auditory stimuli with the former predicting (ie, correlating) the latter. This suggests clear relationship between increased resting state gamma power and reduced task-evoked activity in gamma (see in what follows).…”
Section: Neuronal Findings In Schizophrenia Ib: Abnormal Balancementioning
confidence: 99%